Metal in biological samples from electronic cigarette users and those exposed to their second-hand aerosol: a narrative review - Batista, Diane Rezende [UNESP]; Coelho, Liana Sousa [UNESP]; Tanni, Suzana Erico [UNESP]; de Godoy, Irma [UNESP] (Frontiers, 2024)
Introduction: Electronic nicotine delivery systems (ENDS) are gradually becoming more popular, particularly, among today’s youth. Despite being marketed as safe by the tobacco industry, the notable absence of regulation in their composition is evident. Both the generated fluids and aerosol exhibit a wide variety of substances that are not yet fully identified. In addition to additives, the aerosol contains metals, the presence of which can be attributed to the excessive heating of metallic filaments used in vaporizing the liquid. Objective: This review aimed to identify and describe studies that have assessed metal levels in biological samples obtained from electronic cigarette users and those exposed to their second-hand aerosol. This involved detailing the types and concentrations of metals identified and the biological samples in which the metals were detected. Methods: Two independent researchers conducted searches in the MEDLINE and EMBASE databases to identify studies that measured the metal levels in human non-invasive biological samples from electronic cigarette users and second-hand exposure. Data were presented as a narrative review. Results: In total, 18 articles were included in this review. Overall active and passive exposure to ENDS was related to higher levels of many metals, including lead and cadmium, in biological samples. ENDS users, in general, have lower metal concentrations in biological samples compared to the users of combustible cigarettes. Conclusion: The exposure to primary and second-hand e-cigarette aerosol is related to higher metal concentrations in the biological samples. The adverse effects of this exposure on long-term users are yet to be determined.
Keywords: e-cigarettes; electronic cigarettes; hair; heavy metals; metal; urine; vape